Science Learning: An Analysis Related to Student Learning Activities in Junior High Schools - Rahmayumita, R.; Zulfarina, Z.; Fakhruddin, F. (Journal of Science Education Research, 2024)
Learning activities are all activities carried out by students during the learning process. The study aimed to determine student learning activities in science learning in junior high school. The research used a descriptive method with a survey technique of students in class VIII of SMPN 4 Siak Hulu for the 2023/2024 academic year. The sample was selected using a simple random sampling technique of 60 people. The instrument used a valid student learning activity questionnaire comprising 15 items. The data collection technique was carried out by distributing questionnaires via Google form and analyzed descriptively. The results showed that the average student learning activity was 72.65%, which was high. The highest activity carried out by students was in the visual activity indicator, while the lowest activity was found in the emotional activity indicator. The study concluded that students in class VIII of SMPN 4 Siak Hulu have high learning activity in science learning. Further research is expected to examine the factors that influence student learning activities.